A Design Study for a Multivariable Feedback Control System for Controlling the Air Gap of Maglev Train Suspension System د - Al-NASSIR, IBRAHIM AHMED (2017)
This research present a study of the control of multivariable systems which are subjected to variable input and external load change. The topic of research is to design a controller to control the air gap of the suspension system of a Maglev Train. The design is conducted by implementing a recent research methodology called Least Effort Technique. This methodology were introduced by R. Whalley and M. Ebrahimi in 2006. The significant advantageous of Least effort technique is to reduce the energy consumption in the controller, reducing actuator activity, wear, heat, heat generation, operational and maintenance cost. This research emphasizes this technique enabling comparable transient and disturbance rejection characteristics against results obtained by classical control theories, such as Inverse Nyquist Array and H∞ control theory. The research is focusing on the control problems of the vertical clearance in the suspension system. Initially, the mathematical model of the system is compensated the effect of double integrator which appears in the characteristic equation Simulation of the system is presented to evaluate the effectiveness of the controller to maintain the air gap within the allowable limits, MATLAB-SIMILINK software will be used for simulation purposes and design validation.